Validación de tecnología de cinco insecticidas quìmicos y orgànicos en el control del gusano cogollero (spodoptera frugiperda) del cultivo de maíz (zea mays l.) - Miranda Monar, Heiddy Paola (2016)
The work consisted in validating the effect of five chemical and organic insecticides for the control of the fall armyworm. The research was established in the Department of Plant Protection, Entomology Division, of the National Institute of Agricultural Research (INIAP); under controlled conditions of temperature 25±5 °C, humidity 75 ± 15% and 12:12 hours light: dark. Worm larvae were harvested in petri dishes with corn leaves and artificial diet, after reaching the desired instars (III and IV), were transferred to plastic cups of one ounce, which contained one-inch tender corn leaves and Media previously immersed in the different insecticides under study with high and low doses in 100 ml of distilled water and an absolute control. The variables measured were percentage of leaf consumption and mortality of "Fall Armyworm" (Spodoptera frugiperda Smith) larvae and insecticide efficacy. The percentage of foliar consumption was recorded daily, while mortality was evaluated at 24,48,72,96 and 120 hours from the application of insecticides. The insecticide with the best mortality results (100%) of the mollusc worm was (Spinetoram) Radiant, which demonstrated its effectiveness in eliminating the largest number of larvae for instars III and IV in a shorter time (48 hours), compared to the rest of products tested. There were no statistical differences for Factor B (dose: low and high), because the results showed that the five insecticides used and their corresponding doses do not influence a higher percentage of mortality of the larvae of Spodoptera frugiperda Smith " "Of instars III and IV.The Radiant insecticide (Spinetoram) proved to be economically viable for the small, medium and large producer as it satisfies the control of the worm; Proving to be accessible in the Ecuadorian market, as well as in commercial houses, authorized dealers and agricultural warehouses